The Implementation of Restorative Justice in Cases of Verbal Sexual Harassment - Najwa Salsabila; Kayus Kayowuan Lewoleba (Law Development Journal, 2025)
Verbal sexual harassment is a form of non-physical sexual violence crime as regulated in Law No. 12 of 2022 concerning Sexual Violence Crimes. This action not only degrades the victim's dignity but can also cause prolonged psychological impacts. This research aims analyze the application of the restorative justice principle to the crime of verbal sexual harassment and examine the role of law enforcement officials in its implementation. This research uses a normative-juridical method with a statutory approach and a literature study of primary, secondary, and tertiary legal materials. The results of the research show that although the application of restorative justice is possible based on Police Regulation Number 8 of 2021, Attorney General's Regulation Number 15 of 2020, and Supreme Court Regulation Number 1 of 2024, its implementation cannot be done without careful consideration. This is because the crime of verbal sexual harassment is associated with the victim's immaterial loss, which is difficult to recover merely through a peace agreement. Additionally, there is a risk of victimization if the victim is in a vulnerable position during the reconciliation process. Therefore, a litigation approach should still be prioritized when the victim explicitly desires law enforcement for the sake of certainty and the protection of their rights.